Corporate Governance Factors Affecting Firm Performance in the Media Industry of the Stock Exchange of Thailand (SET): ปัจจัยของการกำกับกิจการที่มีต่อผลการดำเนินงานของธุรกิจดนตรี ที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทยในหมวดธุรกิจสื่อและสิ่งพิมพ์ - Thadsri, Srayoot; Ouppathumchua, Pawat; Boonyam, Treetip (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาถึงปัจจัยของการกำกับกิจการที่มีต่อผลการดำเนินงาน ของกิจการธุรกิจดนตรีที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย ในหมวดธุรกิจสื่อและสิ่งพิมพ์ โดยใช้ข้อมูล อันประกอบไปด้วยข้อมูลจากสื่ออิเล็กทรอนิกส์ที่เกี่ยวกับการดำเนินงานของกิจการ ซึ่งเป็นข้อมูลที่ได้มาจากฐานข้อมูลของตลาดหลักทรัพย์แห่งประเทศไทย และรายงานผลการสำรวจการกำกับดูแลกิจการของบริษัท จดทะเบียนในปี พ.ศ. 2560 โดยใช้เครื่องมือการวิเคราะห์สมการถดถอยแบบพหุคูณ ผลการศึกษาพบว่า ขนาดของคณะกรรมการ, จำนวนครั้งของการประชุมคณะกรรมการในปีดำเนินงาน และระดับคะแนนการประเมินการกำกับกิจการ เป็นปัจจัยที่ส่งผลต่อผลการดำเนินงานของกิจการ โดยขนาดของคณะกรรมการที่ใหญ่ และจำนวนครั้งที่มากขึ้นของการประชุมคณะกรรมการจะส่งผลในทิศทางตรงกันข้ามต่อผลการดำเนินงานของบริษัท และระดับคะแนนการประเมินการกำกับดูแลกิจการจะมีผลในทิศทางเดียวกันกับผลการดำเนินงานของบริษัทอย่างมีนัยสำคัญ ABSTRACT The objectives of this study was to investigate the factors affecting firm performance in the media industry. The data gathered were secondary data from electronic media about the operation of the business. The information was derived from the Stock Exchange of Thailand's database and the results of the corporate governance survey of listed companies in the year 2017. Multiple Linear Regression was used to analyze the data. The study indicated that the size of the committee, the number of committee meetings in a year, and the results of the corporate governance assessment were the factors affecting the firm performance. The size of the big board and more number of board meetings will have a negative impact on the company's performance. The rating of the corporate governance assessment will have a significant positive effect on the company's performance